Evaluation of Intravenous Immunoglobulin Administration for Hyperbilirubinemia in Newborn Infants with Hemolytic Disease - Daniel R. Mohan; Hannah Lu; Jacquelyn McClary; Jaime Marasch; Mary L. Nock; Rita M. Ryan (MDPI AG, 2023)
The primary objective of this research was to evaluate the use of intravenous immunoglobulin (IVIG) in infants with hemolytic disease, to assess compliance with the American Academy of Pediatrics (AAP) guideline recommendations, and to review the data on which the guidelines were based. This retrospective study evaluated all infants in the NICU (neonatal intensive care unit) who received IVIG between January 2018 and December 2020 (n = 71). Total serum bilirubin (TSB) levels surrounding the time of IVIG administration, rate of rise of bilirubin, and direct antiglobulin test (DAT) status were evaluated to determine the appropriateness of IVIG use based on the 2004 AAP recommendations that was current at the time of the study. Fifty-nine infants received IVIG for hyperbilirubinemia. Of them, 80% had an ABO mismatch, 19% had Rh mismatch, and 71% were DAT-positive. Phototherapy was started at an average of 7 h of age, and the first IVIG dose was administered at an average of 13 h of life; nearly 25% received a second IVIG dose. One infant (1.6%) met all three AAP guideline criteria of being DAT-positive, bilirubin within 3 of exchange level, and rising bilirubin despite intensive phototherapy. Twenty-five (42%) babies were DAT positive and met one of the other two criteria. Only 12% (n = 7) had a bilirubin within 3 of exchange level. Most infants who received IVIG for hyperbilirubinemia did not meet the AAP criteria, prompting us to develop an institution-specific IVIG clinical practice guideline. The 2022 AAP guideline was published after our study was completed, but it confirmed our belief that IVIG usage should be more restricted and the criteria more explicit.